The partial mitochondrial genome of Semidalis anchoroides Liu & Yang, 1993 (Neuroptera: Coniopterygidae) - Yaru Zhao; Yanyu Zhang; Guangshuai Liu; Ying Li; Zhiqi Liu (Mitochondrial DNA. Part B. Resources)
Semidalis anchoroides Liu & Yang, 1993 is a small and common insect in southern China. It’s known for its small size, being covered by whitewax powder, and having uncomplicated venation. In this study, the mitochondrial genome for S. anchoroides was sequenced and analyzed. The sequenced partial mitogenome is 15,700 bp in length, encoding 13 protein-coding genes (PCGs), 22 tRNA genes, two rRNA genes, and one partial control region. These findings provide fundamental molecular data, thereby facilitating a more profound understanding of the phylogenetic relationships within the Semidalis species.